Conflict and Labor Markets in Manufacturing : The Case of Eritrea - World Bank (Washington, DC, 2012)
This Dissemination Note draws from the recent Bank report, "Eritrea: Investment Climate Assessment produced by the Africa Private Sector Group." It concludes, in short, that Eritrea is facing a critical labor shortage, partly the result of recent conflict. Mobilization has drained white collar and skilled workers, resulting in high female participation rates, rising wages and declining employment. High unit labor costs are affecting private sector competitiveness and export potential. Swift implementation of the demobilization program coupled with appropriate training is urgently needed.